Rural quality of life - Heike Johansen, Pia (Manchester University Press, 2023)
The 2020 World Happiness Report suggests that rural residents in Northern and Western Europe, North America, Australia and New Zealand are generally happier than their urban counterparts. Similar findings have been reported in country-level studies and broader regional research, especially in Europe. Such findings go against conventional wisdom in the field and represent something of a conundrum to researchers and policymakers alike: the rural–urban happiness paradox. Is quality of life really better in the countryside? How and under which circumstances is this the case? Did influential writers like Edward Glaeser get it all wrong when suggesting that the city had now triumphed? What can we learn from digging deeper in the rural–urban happiness paradox and which critical questions does this leave us with for the future? What might policymakers, planners, architects and other influential actors learn from such an exercise? The purpose of the proposed book is to delve deeper into these matters by asking what quality of life in rural areas is actually all about. Since 2018 a cross-disciplinary team of researchers from four research environments at three Danish universities has been carrying out an ambitious research project to do just that. In this edited volume their findings are presented alongside chapters written by specially commissioned international authors from across Europe, North America, Asia and Africa.